Seasonal Variability of Wind, Surface Current and Sea Surface Temperature in the Eastern Seram Waters During the 2015 Super El Nino - Cipta Utama; Simon Tubalawony; Harold Joppie Davido Waas; Ronald Darlly Hukubun; Marlin Chrisye Wattimena (Nekton, 2025)
The eastern Seram waters are influenced by both the Seram Sea and the Banda Sea. This study aimed to examine variations in wind, surface currents, and sea surface temperature (SST) during 2015, coinciding with the super El Niño event. Data were obtained from the Group for High Resolution Sea Surface Temperature (GHRSST) and the Copernicus Marine Environment Monitoring Service (CMEMS). The results indicated that the monthly average wind speed in this area ranged from 0.01 to 8.98 m/s, with the lowest speed in November and the highest from January and June to September. Surface currents also exhibited seasonal variability, flowing from the Seram Sea to the Banda Sea during the west season (December–January) and reversing eastward in February. During the east season, Banda Sea water masses were supplied by Seram Sea water. Sea surface temperature decreased notably from June to August, with the lowest temperature recorded in August due to upwelling in the Banda and Arafura Seas. Surface currents formed eddies with warm water centers in the northern part of eastern Seram waters, and cold water centers (25,4 °C) were also observed. The convergence of these two water masses with distinct characteristics generated thermal fronts with temperature differences, resulting in strong temperature gradients from August to October as a consequence of upwelling and cooling induced by the intense El Niño at the end of 2015.